Fermented soybean meal modified the rumen microbiota and increased the serum prolactin level in lactating Holstein cows - Zhang, Jiyou; Guan, Feng; Huang, Shana; Ma, Yumin; Wen, Shibao; Jin, Wei; Mao, Shengyong (Frontiers in Veterinary Science, 2024)
This study aimed to investigate the effects of fermented soybean meal (FSM) on milk production, blood parameters, and rumen fermentation and microbial community in dairy cows. In this study, 48 healthy Holstein cows (parity, 3.0 ± 0.6; days in milk, 86.0 ± 6.7) were used. Cows were randomly assigned into four groups (CON, T-200, T-400, and T-600) with 12 cows per group. Cows in CON were not supplemented with FSM. Cows in T-200, T-400, and T-600 were supplemented with 200, 400, and 600 g/head/day FSM, respectively. This study lasted 5 weeks (1-week adaptation and 4-week treatment). The results showed that FSM did not affect milk yield and milk components (p > 0.05). In the serum, FSM greatly increased prolactin (p < 0.01), and a dosage effect was observed. Aspartate aminotransferase and total protein were the highest in the T-400 (p < 0.05), and triglycerides was the lowest in T-200 (p < 0.05), and there was no difference for the 3 measurements between the other 3 groups (p > 0.05). In the rumen, FSM did not affect pH, microbial crude protein, acetate, propionate, butyrate, valerate, total volatile fatty acids and the ratio of acetate:propionate (p > 0.05), only changed NH3-N, isobutyrate and isovalerate (p < 0.05). The results of the rumen bacterial 16S rRNA genes sequencing showed that FSM decreased the richness (p < 0.05) and evenness (p < 0.05) of the bacterial communities. PCoA analysis showed that FSH altered the rumen bacterial community (ANOSIM, R = 0.108, p = 0.002). In the relative abundance of phyla, FSM increased Firmicutes (p = 0.015) and Actinobacteriota (p < 0.01) and Patescibacteria (p = 0.012), decreased Bacteroidota (p = 0.024). In the relative abundance of genera, FSM increased Christensenellaceae R-7 group (p = 0.011), Lactococcus (p < 0.01), Candidatus Saccharimonas (p < 0.01), Olsenella (p < 0.01), decreased Muribaculaceae_norank (p < 0.01). Conclusively, supplemented FSM altered the rumen fermentation parameters and bacterial community, and increased serum prolactin level in lactating Holstein cows. These findings may provide an approach to keep the peak of lactation in dairy cows.